POTENSI KOMPOS SAMPAH DOMESTIK NAGARI AIR HITAM MELALUI PENYULUHAN DAN PEMANFAATAN SAMPAH - Indah Permata Afriani; Nanda Mutia Fadilla; Taufiq Ihsan (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Nagari Air Hitam, Silaut District, Pesisir Selatan Regency, West Sumatra Province is one of the villages that still has not made use of the domestic waste it produces. One of the efforts to utilize domestic waste, especially organic waste, is to recycle this waste into compost products that are marketable. The purpose of this counseling activity is to provide information about the potential for recycling organic waste into compost products in Nagari Air Hitam, Silaut District, Pesisir Selatan Regency, West Sumatra Province. The potential for organic waste that can be processed into compost products was studied through data on waste piles from the 2017 Pesisir Selatan District Waste Periodic Reports and the Population of Nagari Air Hitam. The steps taken are by calculating the waste piles from Nagari Air Hitam, then analyzing the potential for recycling of organic waste that can be composted based on the percentage from the literature. The organic waste produced by Nagari Air Hitam with a population of 1,415 people and a unit of 3.0 L / person / day of waste is 4,245 L / day. Meanwhile, the potential for organic waste to be recycled into compost is 2,037.6 L / day. The results of the analysis of the potential for compost will be conveyed through extension activities and waste utilization. The huge potential for organic waste to be recycled into compost will encourage the community to be able to recycle organic waste into compost.